Development of a Darrieus rotor model for a vertical axis wind farm - Rodríguez-Díaz, Juan Camilo; Espinosa-Sarmiento, Angie Lizeth; Quintero-Gamboa, Yina Faizully (Uptc, 2021)
Using the Buckingham π theorem allows recognizing relevant variables in studies with wind tunnel models. This makes it possible to replicate and reduce prototypes in laboratory models to measure geometric, dynamic, and kinematic values. The mathematical and mechanical development of a Darrieus H rotor for a vertical axis wind farm is presented. In addition, the parametric equations obtained are shown together with the CAD model. Obtaining such a model is based on the downsizing of an existing prototype. Using theoretical-mathematical tools reduces costs and logistics in the development of new technologies and machines.